Comparison of Deep Venous Thrombosis Following Femoral Versus Internal Jugular Catheterization in Hemodialysis Patients - Ahmad, Muhammad Ishfaq; Yasir, Muhammad; Rasheed, Bilal; Mushtaq, Asim; Qureshi, Muhammad Waqas Ahmed; Sheikh, Moniba Saeed (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the frequency of deep venous thrombosis associated with femoral and internal jugular venous catheterization in patients undergoing hemodialysis. Study Design: Prospective longitudinal study. Place and Duration of Study: Department of Nephrology, Pak Emirates Military Hospital, Rawalpindi Pakistan, from Sep 2022 to Feb 2023. Methodology: All patients undergoing hemodialysis, regardless of gender, who were 30-60 years old, were considered for inclusion. Patients were divided randomly. In Group-A, patients underwent hemodialysis through femoral vein catheterization. In Group-B, patients underwent hemodialysis through internal jugular vein catheterization. Following the insertion of the catheter, patients were monitored for any signs of deep vein thrombosis on each visit. Doppler ultrasound examination was conducted before the insertion of the dual-lumen central catheter, subsequent to its removal, and one week following catheter removal. Results: The total of 60 patients were enrolled in the study. Patients who were enrolled in Group-A, had mean age 40.80±8.69 years. Patients who were enrolled in Group-B, had mean age 44.15±9.04 years. In Group-A, 8(26.7%) patients developed deep vein thrombosis. In Group-B, none of the patients developed DVT. The difference in the group was significant (p=0.002). Conclusion: Hence, femoral vein catheterization is linked to a greater risk of DVT than internal jugular vein catheterization.